(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3BNQgG (B:s
(3bGd Ph GdQeI (B: (3EPG Mhd GdXd GdYTi QGjJg MfjakG , hai bQf GdVMi jJfUQ hefgG eG jchf HeYfi GdfSHI Edi GdTF fMh aSbJg hTLYJg cbhdc (B: (3JMQc EPG MQcJg , hJMhd EPG MhdJg cbhdc LQHg hcdeg BNQ GdeLdO GdChd s
(3fSNI JJab ai ChdgG eY Chd fSNI edi edc (B- (3WgQGf (B345 (3HGNJdGa jSjQ ai HYV GdCdaGX HChdgG agQS ddCHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GddZIs